Calculation of microwave parameters of CPW with a buffer layer - Yi Huang (2002 3rd International Conference on Microwave and Millimeter Wave Technology : ICMMT 2002 : August 17-19, 2002, Beijing, China, 2002)
How to calculate the microwave parameters of a co-planar waveguide (CPW) with a buffer layer and thick electrodes has been a standing problem. This subject is of particular interest to electro-optic modulator designers. Although there are quite a few papers having discussed this problem, the suggested. closed-form expressions for calculating these parameters are subject to many restrictions. This paper presents another attempt to tackle this tough problem. First, the existing closed-form expressions are examined carefully. Based on the knowledge gained, a new empirical model is then proposed for calculating the characteristic impedance and the microwave effective index of such a CPW. The calculated results are compared with the results from Ansoft HFSS simulation and published literature. Good agreement has been observed over a very wide range of CPW. This new model seems to be very general, efficient, and accurate.